Spatial gap and two-dimensional decomposition of urban ecological resilience in China - Wan, Qing; Guo, Mengyu; Pan, Fangjie (Frontiers in Built Environment, 2025)
Urban ecological resilience plays an important role in enhancing the ability of urban areas to cope with environmental change and promote sustainable development. On the basis of the panel data of 277 prefecture-level cities in China from 2009 to 2023, a comprehensive evaluation index system of the development level of urban ecological resilience is constructed in this paper. This index system uses three dimensions: resistance, resilience, and adaptability. The criteria importance through intercriteria correlation (CRITIC) weighting method is employed to measure the development level of urban ecological resilience in China, and the Gini coefficient two-dimensional decomposition method is used to analyse the spatial gap and source structure of the development level of urban ecological resilience in China. The study finds that: (1) The overall gap in the development level of urban ecological resilience in China is generally decreasing, with resistance making the greatest contribution to this decrease. (2) The disparity in the development level of urban ecological resilience across China generally tends to decrease; with the exception of the northeastern region, the development level gap of ecological resilience in the eastern, central and western regions has narrowed. (3) From a regional perspective, the interregional gap is the main source of the overall gap. In terms of indicator composition, the resistance gap is the primary contributor to the overall disparity. Considering both regional and indicator compositions, the main source of the overall gap has shifted from the resistance gap between the eastern and western regions to the adaptability gap between the central and western regions.